1920 La. Acts 170, An Act Defining the Crime of Burglary with Explosives and Providing the Punishment Therefor, §§ 1–2. - (:unkn) unknown (General Publisher, 1920)
any persons who, with intent to commit crime, breaks and enters, either by day or night, any building whether inhabited or not, and opens or attempts to open any vault, safe or other secure place by use of nitro-glycerine, dynamite, gunpowder or any other explosive, shall be deemed guilty of burglary with explosives.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME